Persepsi Penggunaan Kosmetik Halal di Kalangan Muslim Generasi Z - Salsabila Rosalia Said; Rania Ariqah Yasir; Robert Kristaung (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study focuses on the perception of halal cosmetics use for Muslim generation z. This study uses a descriptive analysis research method with a quantitative approach. This study uses primary data with data collection carried out by distributing questionnaires to respondents who meet the criteria, namely individuals who use halal cosmetics in the last 3 months and individuals who are included in generation Z. The questionnaire was distributed via Google Forms. The sample used in data processing was 180 respondents who were analyzed using the Structural Equation Modeling (SEM) analysis unit with the AMOS program and also tested the goodness of fit model to test its feasibility. The conclusion obtained from this study is that there is a positive influence between attitude and purchase intention, there is a positive influence between perceived behavioral control and purchase intention, and there is a positive influence between religiosity and purchase intention. However, other results revealed that there was no positive influence between subjective norms and purchase intention.